The functions of phospholipases and their hydrolysis products in plant growth, development and stress responses. (April 2022) - Ali, Usman; Lu, Shaoping; Fadlalla, Tarig; Iqbal, Sidra; Yue, Hong; Yang, Bao; Hong, Yueyun; Wang, Xuemin; Guo, Liang
Abstract: Cell membranes are the initial site of stimulus perception from environment and phospholipids are the basic and important components of cell membranes. Phospholipases hydrolyze membrane lipids to generate various cellular mediators. These phospholipase-derived products, such as diacylglycerol, phosphatidic acid, inositol phosphates, lysophopsholipids, and free fatty acids, act as second messengers, playing vital roles in signal transduction during plant growth, development, and stress responses. This review focuses on the structure, substrate specificities, reaction requirements, and acting mechanism of several phospholipase families. It will discuss their functional significance in plant growth, development, and stress responses. In addition, it will highlight some critical knowledge gaps in the action mechanism, metabolic and signaling roles of these phospholipases and their products in the context of plant growth, development and stress responses.